Students Engagement dan Learning Performance Mahasiswa Pada Mata Kuliah Media Pembelajaran Ekonomi yang menerapkan Metode Project Based Learning - Rani Sofya; Yulhendri Yulhendri; Mentari Ritonga; Nita Sofia (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2021)
This study was conducted to determine the effect of student engagement on learning performance  of instructional media for economic subject students which applied project based learning method. This type of research is descriptive quantitative.  The sample in this study were 30 students of  Instructional media for economic. The data analysis technique used is correlation. The results of this study indicate that the student engagement has a positive and significant effect  on learning performance  of Instructional Media for economic learning students as evidenced by the Sig. (2-tailed) of 0,025 <0,05.